Associations between recently diagnosed conditions and hospitalization due to COVID-19 in patients aged 50 years and older- A SHARE-based analysis. - López-Bueno, Rubén; Torres-Castro, Rodrigo; Koyanagi, Ai; Smith, Lee; Soysal, PINAR; SOYSAL, PINAR; Calatayud, Joaquín (My University, 2021)
Background: Only a few studies have been carried out with a large sample size on the relationship between chronic conditions and hospitalization for coronavirus disease 2019 (COVID-19), and there is no research examining recently diagnosed conditions. Our purpose was to evaluate this association in a large sample including the older population from Europe and Israel. Method: Data from the Survey of Health, Ageing and Retirement in Europe COVID-19 Survey, a representative survey of individuals aged 50 or older residing in 27 European countries and Israel, were retrieved. Associations between recently diagnosed chronic conditions (ie, conditions detected over the last 3 years) (exposure) and hospitalization due to COVID-19 (outcome) were assessed using multivariable logistic regression. Results: A total of 51 514 participants on average 71.0 (SD = 9.2) years old were included. Participants with multimorbidity (ie, 2 or more recently diagnosed conditions) had significantly higher odds for COVID-19 hospitalization (adjusted odds ratio [AOR] = 3.91 [95% CI = 2.14-7.12]). Independent conditions such as lung disease (AOR = 16.94 [95% CI = 9.27-30.95]), heart disease (AOR = 3.29 [95% CI = 1.50-7.21]), or cancer (AOR = 3.45 [95% CI = 1.26-9.48]) showed particularly high odds for hospitalization due to COVID-19. Conclusions: People with recently diagnosed diseases, and in particular those having lung disease, heart disease, or cancer, were significantly more likely to be hospitalized for COVID-19.
Keywords: Diabetes; Hypertension; Lung disease; Multimorbidity; SARS-CoV-2